Promoting Indonesia’s Tourism to China through Public Diplomacy during The Reign of President Joko Widodo - Nur Rahmahwati, Isti; Lestari, Yuliannova (JURNAL ILMU SOSIAL, 2021)
During President Joko Widodo's (Jokowi's) administration, Indonesia and China tend to have closer partnership concerning tourism sector. On the other hand, as Chinese outbound tourists gradually increase year to year, China becomes a key market that is expected to boost international tourist arrivals in Indonesia. The article aims to explain Indonesia’s public diplomacy to China in the tourism sector during the first period of President Jokowi’s administration from the analysis of international relations. This article presents an analysis of Indonesia’s public diplomacy models in enhancing tourism-branding to China based on the soft power theory. Public diplomacy represents a country’s foreign policy through two-way communication and people-topeople interaction between representatives of a country and foreign publics as objects of diplomacy. The article mainly uses qualitative research methodology with analytical and descriptive analysis to understand and analyze public diplomacy and its practical implementations to China. The result finding is that Indonesia makes tourism as a potential soft power to strengthen its identity and enhance strategic and comprehensive relations with China. By developing diplomatic practices through a people-centered approach, the government would be more effective and efficient to reach all levels of Chinese society to promote Indonesia’s tourism